Central Tax Evolution In Indonesia And Islamic Economic Perspective Central Tax - Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This study examines how the evolution or development of Central Tax in Indonesia and how the Central Tax is from an Islamic economic perspective. Descriptive analysis and qualitative data collection were used in this library-based study. This study finds that the current central tax in Indonesia is a development of the tax system that existed since the kingdom era. In the era of the tax empire called